Evaluation of triacetin on mechanical strength and free surface energy of PHBHHx: The prevention of intra-abdominal adhesion - Yildirim, Meryem Akkurt; Demirbilek, Murat; Kizilbey, Kadriye; Kaplan, Engin; Turkoglu, Nelisa (SAGE PUBLICATIONS LTD, 2023)
Several polymers are used for the preparation of biomaterials as membranes and films for tissue engineering applications. The most common plasticizer is PEG to obtain polymer-based biomaterials. On the other hand, triacetin is a non-toxic, FDA-approved plasticizer mostly used in the food industry. In this study, we used triacetin as a plasticizer to obtain hydrophobic membranes for the prevention of intra-abdominal adhesion. We selected a well-known polymer named PHBHHx which is a bacterial polyester generally used as supporting material for cell attachments in regenerative tissue applications. We evaluated the triacetin as a plasticizer and its effect on mechanical, thermal, surface area, pore size, and surface energy. The hydrophobic/hydrophilic contrast of a biomaterial surface determines the biological response. Surface hydrophobicity is critical for the cellular response. The contact angle tests of PHBHHx revealed that the hydrophilicity of the membrane was decreased following triacetin blending. Modification of the PHBHHx membrane by blending with triacetin caused a significant decrease in cell adhesion. The cell attachment rates of PHBHHx membranes were as 95 +/- 5% on the first day, 34.5 +/- 0.9% on third day, and 23 +/- 1.5% on the fifth day, respectively. The rates of cell attachments on PHBHHx/ triacetin membranes were determined as 79 +/- 2.5% for the first day, 33 +/- 2.7% for the third day, and 13 +/- 2.1% for the fifth day, respectively. Besides, triacetin blending decreased the surface area from 38.790 to 32.379 m2/g. The elongation at breaks was observed as 128% for PHBHHx and 171% for PHBHHx/triacetin.
Keywords: Triacetin; adhesion; PHBHHx; surface charge; cell adhesion; PHYSICAL-PROPERTIES; STEM-CELLS; SCAFFOLDS; BIODEGRADATION; BIOMATERIALS; BEHAVIORS; POLYHYDROXYALKANOATES; BIOCOMPATIBILITY; PROLIFERATION; MORPHOLOGY; Biotechnology & Applied Microbiology; Materials Science; Polymer Science